Procedures of corrective maintenance for commercial building / Muhamad Arif Nazman Mohd Nazri - Mohd Nazri, Muhamad Arif Nazman (Universiti Teknologi MARA, Perak, 2022)
Maintaining the building prevents it from deterioration and makes it more resilient over the time. There are many types of maintenance in building maintenance work. Therefore, this report will discuss about one type of maintenance work that have been carried out for commercial building. This report was conducted for the administrative building in Malaysian Veterinary Institute (MVI). This report is aiming to see how the type of maintenance work is carry out and what are the effects and differences achieved after the work is completed. Roughly, the objective of this report is to find out the procedures that have been set to carry out this maintenance work. For overview of this project, this project involves repairing work of the roof, walls, ceiling and interior work for the administrative building. However, these maintenance work is not done all at a time. It is carry out from time to time according to the predetermined schedule. Therefore, this project is very important to give comfort and safety to all users of the building in the future. Moreover, from this report, I am also being able to gain knowledge about building maintenance.